The Impact of Nutritional Supplementation in Selected Chronic Medical Conditions: A Review - Jakub Chodkowski (Quality in Sport)
Introduction: Nutritional supplementation has become an integral part of managing chronic medical conditions, offering potential benefits in improving patient outcomes and quality of life. This review explores the evidence supporting the role of dietary supplements in selected chronic conditions, including cardiovascular disease, diabetes, osteoporosis, and inflammatory disorders, while highlighting potential risks and limitations.